Wideband Non-Linear Vibration Piezoelectric Energy Harvesting Using A Piecewise-Linear Mechanism - Mustaffer, Muhammad Harith; Wan Hashim, Wan Ahmad Faiz; Abdul Rahman, Mohd Nazim; Ramlan, Roszaidi; Putra, Azma (Universiti Malaysia Perlis, 2020)
In recent years, energy harvesting technology has been given a lot of attention due to its capability to produce clean and sustainable energy to power electronic devices. The applications of this technology involve the area of biomedical, automotive, industrial, and even military applications. Currently, the energy harvesting device is made for more than one purpose. Due to similar operating characteristics, apart from tapping the ambient energy, it is also used as the dynamic vibration absorber (DVA). However, the conventional linear mechanism adopted in the system is limited to only in a restricted bandwidth. This paper proposes a newly designed non-linear piezoelectric energy harvesting device which was also adopted as a non-linear DVA (NDVA) by using a piecewise-linear stiffness mechanism. The mechanism consists of a cantilever beam constrained by two limit stoppers, which are adjustable in both horizontal and vertical directions. The restoring forcedeflection behaviour for different limit block configurations was characterised using quasistatic measurement. The dynamic study was conducted for different limit block configurations and input amplitudes. The study on the dynamic behaviour shows that the device can widen the harvesting frequency bandwidth compared to its equivalent linear DVA